ANALISIS PENGARUH TRANSAKSI NON TUNAI DAN SUKU BUNGA BI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Susilawati Susilawati; Dewi Zaini Putri (Universitas Negeri Padang, 2019)
This study to find out how the influence non-cash transactions and interest rate on economics growth. The independent variables of this study is credit cards (X1), e-money (X2) and interest rate (X3). The data used are secondary data in the form of time series from 2010Q1 to 2018Q4, with documentation data collection technique is Bank Indonesia and Badan Pusat Statistik publication, and library studies. The theoretical model of this study is Ordinary Least Square (OLS). The steps in this method is (1) classical assumption test, (2) hypotheses test, and (3) determination coeffisient test (R2). The results of this study show that (1) credit cards significant influence on economic growth in Indonesia, this means that if there is an increase the volume of credit cards transactions,which indicates a velocity of money and increased public consumption, the output and economic growth will also increase.(2) e-money no significant influence on economic growth in Indonesia, this means that an increase or decrease the volume of e-money transactions does not cause or encourage economic growth in Indonesia. (3) the interest rates no significant influence on economic growth in Indonesia, this means that an increase or decrease in interest rates determinated by Bank Indonesia does not affect on economics growth in Indonesia. (4) credit cards, e-money, and the interest rates together have a significant influence on economics growth in Indonesia, this means that if there is a positive change together these independent variables will encourage economics growth in Indonesia.